Trade and competition interlinkages: The case of Telecom - Marco C. E. J. Bronckers (Fondazione Eni Enrico Mattei (FEEM), 1999)
The commitments entered into in the WTO Telecommunications Agreement include a fairly elaborate set of principles designed to encourage and protect competition in this newly liberalising market. This paper analyses these commitments, to see first of all what they mean for the telecommunications sector. In addition, the paper inquires after the implications of these additional commitments for the ongoing debate in WTO whether a more encompassing agreement ought to be drafted on competition law.
Keywords: 330; Internationaler Dienstleistungsverkehr; Telekommunikation; Wettbewerbspolitik; WTO-Regeln; Welt